HALF DIALLEL ANALYSIS FOR F3 GENERATION OF PEA (Pisum sativum L.) UNDER SULAIMANI CONDITION-IRAQ KURDISTAN REGION - & et al., Towfiq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was carried out at Qlyasan  location in Sulaimani region (Lat 35 º 34' 307''; N, long 45º 21' 992; E, 765 masl) for F3 generation of seven pea varieties (1-Avolla, 2-Americana, 3-Jeza, 4-Joneor, 5-Packland, 6-Arvena and 7-Samara). The seeds of 21 F3 crosses and their parents were sown in Completely Randomized Block Design (CRBD).With three replicates. The results showed that the mean squares of genotypes, gca and sca were highly significant for seed weight plant-1 and most its important components. The parents Americana and Jeza recorded maximum values for all studied characters. The cross AvollaxAmericana recorded the highest value for seed weight plant-1 and pod weight plant-1. The cross AvollaxPackland had the highest value for heterosis due to seed weight plant-1 122.114% and whole plant weight 147.111%. The parent Americana recorded maximum positive gca effect value for seed weight plant-1 and some its components pod length, pod weight plant-1 and 100-seed weight. The crosses JezaxArvena recorded maximum positive sca effect value for seed weight plant-1, while the cross AvollaxArvena showed maximum positive sca effect value for pod length and pod plant-1. The average degree of dominance was more than one for all characters indicating to the importance of non additive gene effect in controlling the inheritance of these characters. Heritability in broad sense was high for seed weight plant-1 and some its components pods number plant-1, pod weight plant-1 and 100-seed weight, while it was low in narrow sense for all characters.